2017
DOI: 10.1080/09638288.2017.1416496
|View full text |Cite
|
Sign up to set email alerts
|

Exploring engagement in a virtual community of practice in pediatric rehabilitation: who are non-users, lurkers, and posters?

Abstract: These findings will assist rehabilitation leaders in leveraging rehabilitation-specific virtual community of practice to improve knowledge transfer and practice in pediatric rehabilitation and disability management. Implications for Rehabilitation Communities of practice are increasingly recognized as useful knowledge transfer tools for rehabilitation professionals and are made more accessible thanks to virtual technologies. Our virtual community of practice was found to be optimized in health care organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…For example, Mi (2014) shows how the development of a community of practice allows librarians to extend their traditional role as information provider and take on other roles, such as educator, promoter of interaction and discussion, coordinator for the creation of learning activities, creator of a favourable atmosphere for sharing knowledge, community builder and lifelong learner. As Hurtubise et al (2017) states, virtual communities of practice have been shown to be an effective way of exchanging knowledge, while helping to improve the practice of medicine, although their implementation requires an understanding of user characteristics and of how users employ these platforms, both in the workplace and in their day‐to‐day lives.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mi (2014) shows how the development of a community of practice allows librarians to extend their traditional role as information provider and take on other roles, such as educator, promoter of interaction and discussion, coordinator for the creation of learning activities, creator of a favourable atmosphere for sharing knowledge, community builder and lifelong learner. As Hurtubise et al (2017) states, virtual communities of practice have been shown to be an effective way of exchanging knowledge, while helping to improve the practice of medicine, although their implementation requires an understanding of user characteristics and of how users employ these platforms, both in the workplace and in their day‐to‐day lives.…”
Section: Discussionmentioning
confidence: 99%
“…Esto significa que sus miembros utilizan las tecnologías de la información y la comunicación como su modo principal de interacción, lo que puede incluir redes sociales, aplicaciones web, plataformas o foros en línea, wikis y podcasts (Dubé et al, 2005). Si bien esta característica limita el acceso de aquellos miembros que no utilizan las tecnologías de información, o a quienes no se les hace fácil el manejo de las mismas (Hurtubise et al, 2019), si le permite a la comunidad conectar con Terapeutas Ocupacionales de diversos países, a pesar de las distancias geográficas y diferencias horarias.…”
Section: Una Comunidad De Práctica: ¿Por Qué Existimos Y Cuáles Son L...unclassified
“…More specifically, Endslay et al (2005, p. 29) have identified five types of members within CoP. These participants include the leaders or facilitators who keep dialogues and processes in motion; the experts of the topic with skills or knowledge at centre of the community; those who are considered core members and who are active participants in discussions and activities; the 'lurkers' who may not be regular contributors, but may be key resources of knowledge; and peripheral members who are involved within the group as participants (Hurtubise et al, 2017). It is these peripheral members who gain greater knowledge, identity, and acceptance within the community and they have the potential to move from being at the transient periphery to becoming experts themselves (Birks et al, 2017;Cox, 2005;Johnson et al, 2012;Jorgensen & Hadders, 2015;Li et al, 2009a;Oborn & Dawson, 2010).…”
Section: Communities Of Practicementioning
confidence: 99%